The role of Brazil in the geography of international trade and the effective-ness of the Multilateral Trade System - Vargas Amaral, Renata (2010)
The essay analyses Brazil’s position with regards to the current multilateral trading system. To do so, the authors study Brazil’s recent initiatives to the World Trade Organization (WTO). In particular, they examine Brazil’s stance in the disputes before the Dispute Settlement Body (DSB). Brazil’s recent action in the dispute about cotton question the effectiveness of the WTO system for decisions implementation and discussion of alternatives including the possibility of cross-retaliation in intellectual property rights of the defendant.